CONSTRUCTION BUILT FOR THE BENEFIT OF THE PEOPLE - Talat Turayevich, Halimov (Journal of Learning on History and Social Sciences, 2025)
Objective: This study explores the philanthropic legacy and infrastructural contributions of Chorikulboy Nafasov (1847/1852–1934), a notable figure from Romitan, Bukhara, with a focus on his pivotal role in regional development through the construction of the Chorikulboy Bridge. Method: Employing a historical-comparative approach, this research integrates oral history accounts and archival records to examine the bridge’s construction (1911–1914), architectural design, and socio-economic implications. Results: The analysis reveals that, following restrictions on constructing religious institutions due to skepticism regarding the origins of his wealth, Chorikulboy redirected his efforts toward public infrastructure. Utilizing materials and engineering expertise from Europe, he constructed a hydrotechnical bridge over the Zarafshan River that remains operational today. The bridge not only demonstrated advanced structural durability and resilience against natural elements but also significantly enhanced regional trade and mobility. Novelty: This study offers new insights into Chorikulboy’s transnational construction strategy, which integrated European and local building practices, and positions the bridge as a lasting monument of philanthropy and civil engineering innovation in Central Asia.